Marriage and Fertility Among the Dalit Women: An Age-Specific Study of Sarki Community in Chainpur Municipality, Sankhuwasabha - Bhattarai, Bimal (BARUN Journal, 2024)
In Dalit community, age at marriage is relatively low. There is a close relationship between age at marriage and fertility. This paper examines the relationship between age at marriage and fertility in Chainpur Municipality. Although there are many studies on age at marriage and fertility, no such study has been found in Sarki community. The general objective of the study was to find out the relationship between age at marriage and fertility among the Dalit women namely “Sarki” in Chainpur Municipality Sankhuwasaha. The specific objectives of this study were to find out age at marriage in the Sarki community and to explore the relationship between age at marriage and fertility in this community. This article is based on quantitative design. Data has been collected for ever married-women of age group 15-49 years by using the purposive sampling method. This study has covered 240 ever-married women as a sample. Low age at marriage, more involvement in agriculture, high illiterate population, etc. are the result of the study and the interpretation and analysis of the data have been done in this study. Findings of this study have revealed that the highest percentage of women were married below 20 years. The findings haves indicated that total fertility rate (TFR) is 3.1 per woman which is higher than that of NDHS. This study concludes that early marriage tends to have high fertility.